Accurate Through-Wall Breathing Rate Measurements Using a C-Band FMCW Radar - Rouco, Andre; Pereira, Ana; Filipe Albuquerque, Daniel; Bras, Susana; Pinho, Pedro (IEEE sensors journal, 2025)
This article introduces a novel approach to through-wall breathing rate (BR) detection using a custom-built C-band frequency-modulated continuous-wave (FMCW) radar. Operating within the 4-6-GHz frequency range, the radar leverages the C-band's ability to penetrate dense barriers, such as 30-cm-thick brick and cement walls, with high-resolution capability. Motivated by applications in healthcare and emergency response, this study addresses the need for noninvasive monitoring in scenarios where direct contact is impractical or impossible, such as isolating infectious patients or detecting life in search-and-rescue operations. Unlike traditional methods, this approach incorporates optimized radar settings and an innovative signal processing methodology. This enables accurate measurements without subject movement and allows for real-time applications. Experimental validation involved a diverse dataset of ten subjects, with radar-based BR measurements compared with ground-truth data from the Biopac system. Results demonstrated high accuracy, achieving a mean absolute error (MAE) of 0.07 BPM and a root mean square error (RMSE) of 0.09 BPM. These findings confirm radar robustness in challenging, real-world scenarios, establishing its potential as a cost-effective, reliable solution for through-wall BR monitoring.